Program Kecakapan Hidup Pelatihan Barista Sebagai Upaya Menumbuhkan Motivasi Berwirausaha Pada Peserta Didik Paket C di PKBM Budi Utama Surabaya - Hayati, Fitria Nur; Soedjarwo, Soedjarwo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Skills development is part of life skills which are very important and useful for now and in the future. Life skills are an effort to increase the capacity and capability of every citizen. Skills training programs are very important and useful for students and efforts are needed to improve specific skills or life skills to support getting a job and even to open their own business. Barista training is a service from a non-formal education unit that facilitates learning about drinks and coffee in a relatively short period of time to be used to study various theories and barista skills ranging from basic to expert. This research use desciptive qualitative approach. Data collection is using interviews, observation and documentation. Data analysis techniques use data condensation, data display and drawing conclusions. The results of this study are that the barista training program implemented at PKBM Budi Utama Surabaya runs according to good procedures, the expected output is having entrepreneurial motivation such as high interest, seriousness and commitment. Supporting factors in this study are facilities and infrastructure. The inhibiting factor for barista training is the attendance of participants who are not regular.